An Observational Study of Classroom Acoustical Design and Repetitive Behaviors in Children With Autism. (October 2017) - Kanakri, Shireen M.; Shepley, Mardelle; Tassinary, Louis G.; Varni, James W.; Fawaz, Haitham M.
The objective of the present study is to explore the impact of acoustical design on children with autism in school classrooms. Empirical research on this topic will provide information on how interior space features and spatial environment characteristics can be used to support the learning and developmental needs of children with autism. Specifically, the connection between repetitive behaviors and ambient noise levels in school classroom environments was observed in four classrooms. The occurrence of repetitive motor movements, repetitive speech, ear covering, hitting, loud vocalizations, blinking, and verbally complaining in relation to decibel levels were analyzed using Noldus Observer XT software. As hypothesized, a correlation between noise levels and frequency of target behaviors was found; that is, as decibel levels increased, several of the observed behaviors occurred with greater frequency. Further empirical testing is necessary to test a causal relationship between increased ambient noise levels and autism-related behaviors, and sensory discomfort as a mediator of that relationship. Findings are applied to the development of classroom design guidelines.